Beyond Charity: Social Class and Classism in Counselling - Lavell, E. Fisher (Canadian Journal of Counselling and Psychotherapy, 2014)
Counsellors must work more effectively with working-class and poor people by becoming better informed about social class. A review of current literature suggests that while the working classes represent a substantial proportion of the population, they are not effectively served in counselling. In particular, a lack of class awareness and lack of counsellor attention to the specific needs of working-class and poor clients can compromise the development of therapeutic trust and negatively impact the counselling alliance. Emerging scholarship highlights class-related attitudes and experiences and supports the existence of social class cultures. Implications of a systemic and cultural analysis of social class for counselling practice, training, and research are highlighted. Born to a poor family, the author illustrates some of the complexities of social class by weaving together her personal and professional experience, emphasizing that counsellors must move beyond a charitable desire to help disadvantaged individuals and develop a more nuanced understanding of class and classism.